COVID-19 vaccination in athletes: ready, set, go… - Hull, J. H.; Schwellnus, M. P.; Pyne, D. P.; Shah, A. (The Lancet Respiratory Medicine, 2021)
In the fight against the COVID-19 global pandemic, the focus in 2021 has fortunately turned to vaccination strategies. The successful development of several vaccines, and their proven efficacy and short-term safety in large scale multinational trials against severe acute respiratory syndrome coronavirus 2 (SARS-CoV2), offers promise in controlling the pandemic. Many countries are now operationalising their vaccination programmes, and prioritising health-care workers and the most vulnerable individuals within the population—eg, the elderly and those with chronic health conditions. In the sporting world, COVID-19 has curtailed normal activities considerably and led to the postponement and cancellation of a vast number of national and international events. Several studies within the past year detail COVID-19 transmission occurring in sport, and while the delivery of rigorous infection control procedures is central in preventing SARS-CoV2 transmission, the issue of COVID-19 vaccination in elite and competitive, recreational athletes is fast becoming a pressing issue for individual athletes, sporting teams, and organisations. Sport clinicians are now facing several important considerations, including the impact of exercise on efficacy of vaccines, the potential side effects, the best type of vaccine for a given athlete or group of athletes (if choice becomes relevant), advice regarding the timing of vaccination, and finally whether vaccination prevents SARS-COV-2 transmission.